MINUMAN FUNGSIONAL SERBUK INSTAN JAHE (Zingiber officinale R.) DENGAN PENAMBAHAN SARI UMBI BIT (Beta vulgaris L.) SEBAGAI PEWARNA ALAMI - ADITYA ADITYA; AKHYAR ALI; DEWI FORTUNA AYU (Universitas Riau, 2018)
Ginger and beet root can be used as ingredients in functional drink. This research aimed to know the bestformulations of ginger and beet root for the quality of functional drink. Research method used CompletelyRandomized Designed which consisted of five treatments and each treatment was repeated four times.Treatments of ginger extract and beet root extract were 100%:0%, 90%: 10%, 80%:20%, 70%:30%, and60%:40%. Data were statistically analyzed by using Analysis of Variance and continued with Duncan’s NewMultiple Range Test at 5% level. Results of analyzed showed that the ratio of ginger and beet root extractsignificantly affected water content, ash content, reducing sugar content, antioxidant activity, color, aroma,and flavour. Based on this research, the best treatment was the powder with ginger and beet root extract70%:30% which had average of water content 2.54%, ash content 1.41%, and reducing sugar content13.36%. Sensory assessment of functional drink by panelist showed that the drink had a red brick color, alittle ginger and beet root scented, and rather smooth.